Pemanfaatan Canva dalam Pembelajaran Interaktif: Kajian Kualitatif - Netti Herawati; Nuryani Nuryani; Abiyasa Eka Saputra (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research aims to explore the use of Canva as an interactive learning medium at the elementary school level. Canva, an easy-to-use graphic design platform, offers great potential to create engaging, creative, and visual learning experiences for students. This study uses a qualitative approach with a case study method involving grade IV students in an elementary school as research subjects. Data collection techniques include observations, interviews with teachers and students, and documentation of student work using Canva. The results of the study show that the use of Canva can increase student interactivity, creativity, and motivation to learn. Students actively participate in learning, mainly when creating posters, infographics, or presentations describing the concepts being taught. Material comprehension has also improved, especially on topics that require visual representation. While several obstacles are related to device access and student adaptation time, the benefits of using Canva in learning are significant. This study suggests that teachers should regularly integrate Canva into their learning to improve the student learning experience and provide training on how to use Canva to maximize its use. Further research is needed to examine the long-term impact and compare it with other interactive learning media